Ecology of the Porcupine caribou herd - Whitten, Kenneth R. (Rangifer, 1996)
Researchers have described general patterns of population regulation that fit most caribou (Rangifer tarandus) herds. Nevertheless, specific factors operating on particular populations vary greatly, and efforts to categorize herds according to the general patterns often lead to confusion. It is difficult for biologists to attempt to describe population dynamics in terms of density relationships for wide-ranging arctic caribou such as the Porcupine Herd. In these herds density varies as a function of dispersal and erratic movement patterns and is not simply the number of caribou divided by a fixed range area. Density is also a poor surrogate for resource availability per individual caribou because climatic factors affect forage and/or access to forage independendy of caribou numbers. Thus classic signs of nutritional stress such as delayed puberty, reduced productivity, and winter starvation can occur when a population is small as well as large and do not necessarily denote food competition brought on by high density, per se. Nutritional stress and exacerbated predation due to adverse weather conditions occasionally cause the Porcupine Herd to decline, and limiting factors such as poor nutrition, predation, harvest, accidents, and disease act in combination to keep herd growth rates low during periods of good weather. Adverse weather setbacks occur frequently, and the herd remains within a fairly restricted range of densities over long time periods. There is no true density dependent regulation and no equilibrium in this system.